Task shifting from general practitioners to nurses in out-of-hours primary care: an explorative case study of team-based practices - Katrine Bjørnshave Bomholt; Anna Mygind; Mette Amalie Nebsbjerg; Morten Bondo Christensen; Linda Huibers; Viola Burau (Scandinavian Journal of Primary Health Care)
Background Out-of-hours primary care (OOH-PC) is essential for treating urgent health problems. However, the high demand for these services has increased the workload.Objective To investigate the interprofessional collaboration in OOH-PC and task shifting from general practitioners (GPs) to nurses, specifically the professional practices and the perceived experiences of GPs and nurses.Methods This explorative case study was based on observations and interviews, using normalisation process theory as the theoretical framework. Observations were conducted in two OOH-PC clinics in the Central Denmark Region, followed by individual semi-structured interviews with five GPs and six nurses working in these clinics. Data were collected from March to October 2022.Results GPs and nurses worked together in a team-based workflow based on different roles and skills but joint tasks. The nurses handled patients with injuries and performed diagnostic tests. A team-based workflow with task shifting was supported by familiarity within the team, with nurses performing informal coordination tasks and having formal support like protocols, training, and GP supervision. GPs and nurses appreciated the team-based workflow, as it facilitated efficient resource use and high job satisfaction. However, both groups expressed concerns about the sustainability of OOH-PC clinics.Conclusion Task shifting from GPs to nurses in OOH-PC is feasible in a team-based workflow, resulting in efficient use of available resources and high job satisfaction. However, task shifting should not aim to replace GPs with nurses. Instead, their roles and skills should be seen as complementary, which calls for task sharing.